A study on teacher motivation levels based on intrinsic and extrinsic motivation factors - Gökyer, Necmi (Sakarya University, 2016)
The aim of this study was to examine the motivation levels of elementary, secondary and high school teachers from public schools in Elazığ, Turkey based on intrinsic and extrinsic motivation factors. The degrees of impact that intrinsic and extrinsic motivation factors have on teacher motivation were investigated in different work places and places of duty. Teachers’ motivation levels were studied based on Herzberg’s dual factor theory. As the intrinsic factor, teacher views on motivation factors and their satisfaction levels were measured. The study group included 771 randomly selected teachers who were working at public elementary, secondary and high schools located in the center, districts and villages of Elazığ. These teachers were asked to respond to Kelecioğlu, Bilge and Akman’s (2006) Teaching Staff Work Satisfaction Scale (TSWSS). The findings showed that male teachers had higher intrinsic and extrinsic motivation than females. There was no difference between the intrinsic and extrinsic motivation levels of teachers aged differently. Single teachers had higher intrinsic and extrinsic motivation levels than married teachers. Furthermore, social sciences teachers had higher intrinsic satisfaction scores than science teachers. Both intrinsic and extrinsic motivation levels were higher among teachers with 1-5 years of work experience than those with 6-10 years of experience. Finally, teachers working at the city center had higher intrinsic and extrinsic motivation levels than those located in villages. © The Turkish Online Journal of Educational Technology.
Keywords: Extrinsic motivation; Instinct motivation; Job satisfaction; Motivation